What stalls a renewable energy industry? Industry outlook of the aviation biofuels industry in Australia, Germany, and the USA. (December 2018) - Dodd, Tracey; Orlitzky, Marc; Nelson, Tim
Abstract: Despite the global aviation industry's strong endorsement of a switch to aviation biofuels, fossil fuel remains the dominant energy source for air travel. Drawing on a multiple case study of 58 organizations in the emerging aviation biofuels industry relevant to Australia, Germany, and the USA, we unpack the lessons learned from this stalling industry. First and foremost, we identify a key difference in industry outlooks and corresponding strategic mindsets. Specifically, the two outlooks—industry optimism and industry pessimism—seem to correspond to specific strategic mindsets. Whereas industry optimists (1) stressed diversification, (2) were demand-driven in their decisions about R&D, and generally (3) had a learning orientation to innovations, industry pessimists emphasized the need for (1) premium pricing, (2) government intervention, and (3) economies of scale as key drivers of industry development and growth. We also found geographic differences in industry outlooks among biofuel entrepreneurs and other stakeholders in Australia, Germany, and the USA. Through our findings, we offer insights for policymakers and other industries seeking to transition to renewables. Highlights: Innovators' industry outlook and endorsed sustainability strategies interdependent. US entrepreneurs most optimistic about prospects of aviation biofuels. Skepticism about prospects of biofuels most widespread among Australian respondents. Pessimistic respondents stressed need for government interventions the most.